Social and Employment Policy Trends in the European Union and their Impact on Lithuanian Social Law - Petrylaitė, Daiva; Petrylaitė, Vida (Teisė, 2024)
The article addresses Lithuania‘s compliance with labour, employment, and social policy laws of the European Union (EU) after its accession to the EU. It highlights the significance of social and employment policies within the EU framework, as noted in the Lisbon Strategy and the European Pillar of Social Rights, and emphasises the continuous need to update national legislation to conform with expanding EU regulations.The authors examine legislative advancements in the European Union throughout the previous ten years, examining social policy patterns and obstacles, including the COVID-19 pandemic, migration, and the economic downturn of 2007–2008. With an emphasis on the difficulties of the last ten years, they want to evaluate the development of social policy and labour law in the EU and in Lithuania.According to the article, during the past decade, the EU has changed its approach to social policy and labour relations, from harmonisation to coordination. Recent European Commission proposals focus on economic matters, with a growing emphasis on the use of soft-law measures for social regulation. The EU‘s equal opportunities policy is changing, especially with regard to gender equality and work-life balance. The European Commission is pushing for legislation to improve work-life balance options, such as parental and paternity leaves. The goal of the EU Minimum Wage Directive 2022/2041 is to end wage dumping and reduce poverty among workers, especially those earning the minimum wage. It creates procedural principles for minimum wage setting in Member States but does not impose a uniform minimum pay level throughout the EU. Lithuania will have difficulty implementing this directive into national legislation, nevertheless, as its current collective bargaining and minimum wage models might not adhere to the directive‘s standards.
Keywords: labour law; social policy; paternity leave; reconciliation of work and family responsibilities; minimum monthly wage